STRATEGI PENGOLAHAN LIMBAH BATANG POHON AREN (ARENGA PINNATA) MENJADI PRODUK MEBEL - I Wayan Sudana (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
The existence of wood as raw material for furniture increasingly scarce and expensive, so it needs to be an effort to find new types of furniture materials. On the other hand, waste palm trees (Arenga Pinnata) potentially used as material quality and unique furniture, but not taken so discarded as trash. This study aims to analyze the characteristics of the palm tree and find a strategy processing into furniture products. This study uses a qualitative method. Data were collected through observation, testing, and literature. Data were analyzed interactively through data reduction, data display, and conclusion. The results of the identification and analysis of the characteristics of palm tree found processing strategy palm trees into furniture with some systematic steps, namely: 1) the creation of design basic shape with the application of theconcept of “tubes” (cylinders) and creation of ornament design by applying the concept of “ukir tatah”; 2) the preparation of materials such as palm trees and wooden boards; 3) provision of means of production is complete; 4) the creation of a basic form of furniture; 5) creation of ornaments as decoration; 6) The assembly of the ornaments on the basic form of the collage technique; 7) finishing (natural, staining, or antique); 8) the evaluation of the product. If this strategy is applied, then the palm trees can be utilized as a furniture products are unique and good quality.